Prepare for IELTS. The IELTS preparation course = Tài liệu luyện thi chứng chỉ IELTS - Cameron, Penny; Lê Huy Lâm (Tp.HCM : Nxb Tp.HCM, 2000)
The manifest purpose of a course for a specific test is to give students the background knowledge and pratice material in the prescribed format to enable them to obtain acceptable scores on the test itself.
Keywords: IELTS; English language -- Study and teaching